Michael Winter, 1934-2020. - HATINA, MEIR; LEVANONI, AMALIA (Mamluk Studies Review, 2020)
His works reveal him to be a meticulous and sensitive social historian who carefully examined the 1 Michael Winter, Society and Religion in Early Ottoman Egypt: Studies in the Writings of Abd alWahhab al-Sha rani (New Brunswick, 1982). Winter was highly prolific in a variety of fields but concentrated in particular on Egypt and Syria under the Mamluks and the Ottomans. 2 Winter's unique combined study of the Mamluk and Ottoman empires was acknowledged in a volume published in his honor by A. Ayalon and D. J. Wasserstein (eds.), In The Mamluks in Egyptian and Syrian Politics and Society, edited by Michael Winter and Amalia Levanoni, 297-316.